Water, Health, Food: Operationalizing One Health to understand socio-ecological system dynamics in pastoral communities in northern Kenya - Thomas, Sirimon (Jameel Observatory for Food Security Early Action, 2024)
Presented at Jameel Observatory for Food Security Early Action Community of Practice meeting, Nairobi, 14-15 May 2024